TA’WIL TERHADAP AYAT AL-QUR’AN MENURUT AL-TUSTARI - Abidin, Umar (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2014)
The article that is written by Umar Abidin discusses al-Tustari’s theory of ta’wīl and his interpretation of certain verses, which can be called ta’wīl. According al-Tustari, every word of the Qur’an has four kinds of meaning: zahir (exoteric meaning), batin (essoteric/hidden meaning), hadd (legal meaning) and matla‘ (deepest meaning). An attempt to grasp the hidden and deepest meaning is called ta’wīl . In order to elaborate al-Tustari’s ta’wīl, the author of this article also discusses his interpretation of Surat al-Nur: 35. In conclusion, Abidin says that al-Tustari had made a significant contribution to the sufistic interpretation of the Qur’an.